Crystal Growth of the Quasi-2D Quarternary Compound AgCrP2S6 by Chemical Vapor Transport - Sebastian Selter; Yuliia Shemerliuk; Bernd Büchner; Saicharan Aswartham (Crystals, 2021)
We report optimized crystal growth conditions for the quarternary compound AgCrP<semantics>2</semantics>S<semantics>6</semantics> by chemical vapor transport. Compositional and structural characterization of the obtained crystals were carried out by means of energy-dispersive X-ray spectroscopy and powder X-ray diffraction. AgCrP<semantics>2</semantics>S<semantics>6</semantics> is structurally closely related to the <semantics>M2</semantics>P<semantics>2</semantics>S<semantics>6</semantics> family, which contains several compounds that are under investigation as 2D magnets. As-grown crystals exhibit a plate-like, layered morphology as well as a hexagonal habitus. AgCrP<semantics>2</semantics>S<semantics>6</semantics> crystallizes in monoclinic symmetry in the space group <semantics>P2/a</semantics> (No. 13). The successful growth of large high-quality single crystals paves the way for further investigations of low dimensional magnetism and its anisotropies in the future and may further allow for the manufacturing of few-layer (or even monolayer) samples by exfoliation.